Landasan Teoretis: Tinjauan Linguistik, Psikolinguistik, dan Sosiolinguistik dalam Penyusunan Materi Pembelajaran Bahasa Arab - Muhammad Rahmat Alimin; Sulfadli Sulfadli; Ahsan Takwim; Muhammad Fathin Haqqar; Hamzah Hamzah; Kaharuddin Kaharuddin (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2026)
The development of Arabic learning materials requires a strong theoretical foundation so that the materials can help students understand the language effectively. This article aims to explain the role of linguistics, psycholinguistics, and sociolinguistics as the theoretical basis in the preparation of Arabic learning materials. The method used in this article is a literature study by reviewing various sources related to the development of language learning materials. The results of the study show that linguistics provides an understanding of the structure of the Arabic language, including sounds, word formation, sentence structure, and meaning. Psycholinguistics helps explain the process of language learning experienced by students so that learning materials can be designed according to their abilities and stages of development. Sociolinguistics explains the relationship between language and society so that learning materials can be adapted to the social and cultural context of language use. By integrating these three perspectives, Arabic learning materials can be developed in a more systematic, understandable, and relevant way to meet the needs of students.